Pengembangan Knowledge Management Berbasiskan Talent Management untuk Mendukung Knowledge Culture - Muljo, Hery Harjono (Bina Nusantara University, 2011)
Every organization needs to realize that the inside knowledge should be used efficiently and effectively, and also should get support from knowledge culture. The purpose of the writing is the development of knowledge management based on talent management to support the existence of knowledge culture. The method used is through survey, interview, direct observation and literature study. Survey and interview had been done in Talent Management BINUS University, especially in Learning and Department (L&D) unit. The direct observation is through key performance indicator of lecturers. The literature study is through exploring scientific journals, especially related to the topic of knowledge management through website. The result is that it could be concluded in strategy of policy and award rewarded used to approach knowledge management development in supporting knowledge culture.Â